The Image Of Manahan Region - Ita Dwijayanti; Andi Dwi Nugroho (Journal of Architectural Research and Design Studies, 2018)
Architects should have great knowledge as well as broad perspective when planning a project in a big scale (or in macro scale e.g. public buildings). The good knowledge insight is important to recognize and understand two important things: (a) Architecture of City, and also (b) Urban Design. In both fields, an understanding of the background, context, and aspects of architectural design is important to have. A city area basically can be built from a structure or mass customization of buildings that are well designed individually or entirely. Urban planning has at least three main objectives and concerned with (a) security, (b) comfort and (c) beauty (aesthetics). Manahan is considered as one of the images of the Solo because it has an epic history, infrastructure, technology, and green open spaces that are able to facilitate all circles of society both in education and tourism. The qualitative method was applied in this study with two data collection methods, that were (a) observations & direct fields survey around Manahan Region, and (b) capturing photographs of potential buildings that support the urban area. The topical and visual analysis of architecture descriptive was also applied as analytical method upon the obtained data. The result of this analysis is a brief description that Manahan potentially provides culinary zone, educational, offices and services space, and also sport facilities equipped with good infrastructure. A statue of Soekarno (First President of Republic of Indonesia) shows the image of educated and cultured Manahan.Keywords: Image, Manahan, Solo